Proceso de atención nutricional en paciente masculino de 59 años de edad con insuficiencia cardíaca y diabetes mellitus tipo 2. - Gutiérrez Pérez, Tanya Jessenia (2022)
Heart failure is a chronic pathology that degenerates the heart in which the heart does not pump enough blood, preventing oxygen from reaching the body, causing fatigue and accumulation of blood that, if it were to leave the blood vessels, would cause congestion in the lungs. Diabetes is a long-term chronic non-communicable pathology that occurs when the pancreas does not produce enough insulin, or once the body does not use the insulin produced by the body in the correct way, causing a production in the levels of glucose present in the blood that throughout the disease will cause a lot of damage to the nerves and blood vessels. In this clinical case, the nutritional process that will be applied to a 59-year-old patient who was admitted to the general hospital of Quevedo due to presenting a clinical picture of stabbing left chest pain of a month of evolution accompanied by dyspnea will be observed. mild exertion and nausea. Patient with diabetes mellitus II diagnosed 5 years ago with irregular treatment was referred to the internal medicine ward where he was admitted for treatment, he was referred to nutrition where he was assessed and biochemical data was reviewed where the patient had high glucose levels, cholesterol and triglycerides. With nutritional treatment, the nutritional status of the patient will be improved and in the same way glucose, cholesterol and triglyceride levels will be improved.